Faktor-Faktor yang Berhubungan dengan Kunjungan Antenatal Care (ANC) K1 pada Ibu Hamil di Puskesmas Baruharjo Kabupaten Trenggalek - Alberta Surya; Ernawati Ernawati; Andriyanti Andriyanti; Atika Atika (Yayasan Jompa Research and Development, 2026)
Background: Maternal mortality rates in Indonesia remain high, with the main causes of maternal death being hemorrhage, infection, and hypertension. One effort to reduce maternal mortality rates is to increase the coverage of Antenatal Care (ANC) visits. The first ANC visit (K1) in the first trimester is very important for detecting pregnancy risks and providing early treatment. The purpose of this study was to analyze the factors that influence the first ANC visit (K1) at the Baruharjo Community Health Center in Trenggalek Regency. Methods: This study used a cross-sectional design with a sample of 81 pregnant women selected using purposive sampling. Data were collected using a questionnaire and analyzed using the chi-square test. Results: The chi-square test showed that the variables associated with the first ANC visit were age (p=0.018), knowledge (p=0.025), occupation (p=0.021), parity (p=0.049), husband's support (p=0.020), and family support (p=0.08). Meanwhile, education (p=0.740) and income (p=0.251) were not related to the first ANC visit. Conclusion: Factors that influence the first ANC visit (K1) are maternal age, maternal knowledge, parity, occupation, family support, and husband support. The 20–35 age group had the best K1 coverage. Education and family income were not associated with K1 attendance.